The Models of Engaged Learning and Teaching Connecting Sophisticated Thinking from Early Childhood to PhD - Willison, John (SpringerBriefs in Education,, 2020)
This book provides a practical philosophy for promoting students' sophisticated thinking from Early Childhood to PhD in ways that explicitly interconnect across the years of education. It will help teachers, academics and the broader learning and teaching community to understand and implement these connections by introducing a conceptual framework, the Models of Engaged Learning and Teaching (MELT). By covering the nature, philosophy, practice and implications of MELT for teachers and students alike, the book will help teachers to facilitate students' awareness of, and increasing responsibility for, the thinking demanded by subject and discipline-specific learning as well as interdisciplinary learning, whether face to face, online or in blended modes. The book will also provide educators with ways to effectively engage with complex, and sometimes conflicting, contemporary educational concepts, and with a diverse variety of colleagues involved in the learning and teaching enterprise. The book provides guidance that allows curriculum improvement, teacher action research and larger-scale research to be reported on from a common perspective, bridging the gap between those readers focused on research and those focused on teaching. The book shares valuable insights and ways of addressing the contemporary issue of discipline-based learning versus transdisciplinary learning, reducing the dichotomy and enabling the two approaches to complement each other. This is an Open Access book.